Integration of computation methods in dosimetry of radiation processing - Lazurik, V.T.; Lazurik, V.M.; Popov, G.F.; Rogov, Y.V. (Вопросы атомной науки и техники, 2008)
Software for modelling by Monte Carlo (MC) method the dosimetric devices such as dosimetric wedge (ModeDW) and stack (ModeStEB) irradiated with scanned electron beam on moving conveyer was developed by authors. Integration of computer modelling of a dose distribution in films located in a wedge and stack made of arbitrary materials expands the procedure opportunities of the dosimetric devices in the dosimetry of radiation processing.